Management compliance attention, social performance and pay gap: Evidence from China. - Fei Han; Yong Jiang; Yanhan Sun (PLoS ONE)
The pronounced pay gap prevalent in companies has raised critical concerns regarding organizational equity. This study investigates mechanisms to mitigate pay gap through the lens of management compliance attention, with the dual objectives of enhancing intra-firm distributive justice and fostering sustainable organizational development. Furthermore, this study employs a comprehensive methodology, including textual analysis of annual reports to construct management compliance attention variables and the Chinese Huazheng ESG rating system to measure social performance. The results show that:(1) Management compliance attention is negatively correlated with pay gap(β = -0.010,p < 0.01); (2) Social performance is negatively correlated with pay gap(β = -0.035,p < 0.01); (3) Social performance strengthens the negative effect of management compliance attention on pay gap(β = -0.022,p < 0.05). Based on the results, we find that management compliance attention and social performance can narrow pay gap respectively, and that social performance positively moderates the relationship between compliance attention and pay gap. In addition, organizational resilience is identified as a partial mediator, explaining how compliance attention enhances firms' ability to adapt to external changes, thereby reducing pay gap. Heterogeneity analysis shows that management compliance attention and social performance effectively narrow pay gap in state-owned shareholding companies, and widen pay gap in private shareholding companies. This study contributes to the literature on the economic consequences of corporate compliance and social performance and the determinants of pay gap. Practical implications involve recommendations for firms to strengthen corporate compliance systems, enhance social performance and organizational resilience, and establish transparent compensation frameworks.